Women's management practices and performance in rural female-owned family businesses. Issue 2 (10th July 2017) - Peake, Whitney; Marshall, Maria I.
Abstract : Purpose: Prior research indicates that family businesses have fewer management control practices in place and are more likely to have non-economic goals for their firm. Further, researchers in this domain contend that female-controlled businesses tend to underperform compared to male-controlled businesses. The purpose of this paper is to analyze the performance effects of management controls and goals for the business across both male and female-controlled farm and rural family businesses. Design/methodology/approach: The data used in the analyses are from the 2012 Intergenerational Farm and Non-Farm Family Business Survey. The sample comprises 576 small- and medium-sized rural family businesses. The authors used probit analysis to model both family business objective and subjective success for women and men. Findings: The results suggest that female-controlled farm and rural family businesses do not underperform their male counterparts in terms of objective or subjective assessments of performance. The results do indicate, however, that strategic management via management control practices within the firm influence objective and subjective performance differently across male and female-controlled farm and rural family businesses. Originality/value: The results provide three primary contributions to the family business literature. First, the authors determined that strategic management practices via management control mechanisms, as well as the monitoring of managers, are of significance to the objective performance (i.e. gross income) of both men and women-controlled farm and rural family businesses. Second, the authors found that communicating economic vs non-economic goals do not influence satisfaction with the firm's performance, but do influence the probability of success for female-controlled family businesses. Finally, the authors find that when we compare male and female-controlled businesses in the same industry, while controlling for family and business factors, men and women do not differ in a statistical sense in objective or subjective performance.